2021
DOI: 10.1152/ajplung.00159.2021
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6, a therapeutic target for pulmonary hypertension

Abstract: Idiopathic pulmonary arterial hypertension (PAH) is a fatal and progressive disease. Pulmonary vasoconstriction due to pulmonary arterial smooth muscle cell (PASMC) contraction and pulmonary arterial remodeling due to PASMC proliferation are causes for increased pulmonary vascular resistance in patients with PAH. We and others observed upregulation of TRPC6 channels in PASMC from patients with PAH. An increase in cytosolic Ca2+ concentration ([Ca2+]cyt) in PASMC triggers PASMC contraction and vasoconstriction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 137 publications
(216 reference statements)
0
20
0
Order By: Relevance
“…Recently, Jain et al demonstrated that oral gavage with TRPC6 blocker BI-749237 reduced the development of PH induced by CH exposure in mice [ 191 ], suggesting that TRPC6 could be a potential target in PAH.…”
Section: Soce In Pahmentioning
confidence: 99%
“…Recently, Jain et al demonstrated that oral gavage with TRPC6 blocker BI-749237 reduced the development of PH induced by CH exposure in mice [ 191 ], suggesting that TRPC6 could be a potential target in PAH.…”
Section: Soce In Pahmentioning
confidence: 99%
“…In this study, 2-APB was administered with osmotic pumps at a delivery rate of 10 mg/kg per day, which is similar to the daily dose range used by Smith et al (2015) , Castillo-Galán et al (2016 , 2022) and Jain et al (2021) to block STOC in vivo . Indeed, Smith et al (2015) treated chronic hypoxic mice with 2-APB (1 mg/kg/day i.p.)…”
Section: Discussionmentioning
confidence: 99%
“… Castillo-Galán et al (2016 , 2022) , administered 2-APB (10 mg/kg/day i.v.) to neonatal lambs with a partial or full gestation in high altitude to ameliorate the pulmonary hypertension and vascular remodeling, and Jain et al (2021) administrated 2-APB (1 mg/kg per day i.p.) to attenuate pulmonary hypertension in hypoxic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung, another current subject in search for treatment options, increased TRPC6 responses of smooth muscle and vascular endothelial cells are associated with acute hypoxic vasoconstriction [ 13 ] but also with idiopathic pulmonary arterial hypertension (IPAH) [ 14 ] and lung ischemia-reperfusion edema (LIRE) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%